The Prevalence of Abnormal Pap Smears in females Referred to Health Centers Affiliated to Medical Sciences During the Years 2012 to 2016 - Zahra Massomi; Somayeh Khani; Maryam Gharosian; Maryam Farhadian; Arezo Shayan (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Cervical cancer is one of the most important female reproductive system diseases. The aim of this study was to estimate the prevalence of abnormal Pap smears of pregnant females in public health centers and hospitals of Hamadan. Materials and Methods: In a retrospective study, 36046 Pap smears of females was extracted from the records referred to government health centers affiliated to Hamadan University of Medical Sciences and Fatemiyeh Hospital Hamadan, between 2012 and 2016. After checking the results of Pap smear, abnormal information (605 cases) were collected and investigated. Data were then analyzed using the SPSS21-software and descriptive statistics and one-way Analysis of Variance (ANOVA). Results: The majority of females with abnormal Pap smear results (%30.4) were aged 45 to 36 years, and %48.6 of females with abnormal Pap smear had parity (1-3). From a total of 36046 cases, 605 cases of abnormal Pap smear were observed. The highest and lowest frequencies of abnormal Pap smear were related to ASCUS and LSIL, at a prevalence of %78 and %1, respectively. There was a positive relationship between abnormal Pap smear results and age (P = 0.037). Conclusions: The prevalence of abnormal Pap smear in Hamadan was %1.67. Malignant cervical cancer and invasive cancer risk increased with age, hence, screening and Pap smear, especially from age 35 and above, is recommended.